Stroke Telemedicine - Demaerschalk, Bart M. (Mayo Foundation for Medical Education and Research, 2009)
Stroke telemedicine is a consultative modality that facilitates care of patients with acute stroke at underserviced hospitals by specialists at stroke centers. The design and implementation of a hub-and-spoke telestroke network are complex. This review describes the technology that makes stroke telemedicine possible, the members that should be included in a telestroke team, the hub-and-spoke characteristics of a telestroke network, and the format of a typical consultation. Common obstacles to the practice of telestroke medicine are explored, such as medicolegal, economic, and market issues. An example of a state-based telestroke network is thoroughly described, and established international telestroke networks are presented and compared. The opportunities for future advances in telestroke practice, research, and education are considered.